Evolução cromossômica na família Lebiasinidae (Teleostei, Characiformes), com enfoque em espécies do gênero Lebiasina - Sassi, Francisco de Menezes Cavalcante (2020)
The Lebiasinidae family is composed by seven genus of small freshwater fishes that can be found in small rivers of Central and South America. Members of this family presents a great diversity in form and body color, but their evolutionary relationships are still unclear. Our objective was to realize the first cytogenetical analysis in two species of Lebiasina genus, aiming to clarify their karyotypic characteristics and their chromosomal evolution. For this, Lebiasina bimaculata and L. melanoguttata presents 2n = 36 as their diploid number, exclusively composed by bi-armed chromosomes. The C-positive heterochromatin was located in centromeric and telomeric regions of several chromosomes in both species. But, in L. melanoguttata there is a remarkable interstitial series of c-positive heterochromatin, absent in L. bimaculata. The rDNA 5S is located in the interstitial region on q-arm of the first chromosomic pair in both species, with an additional site on telomeric region of 13 chromosome of L. melanoguttata. The 18S rDNA can be found in telomeric region of the third pair in L. bimaculata, while L. melanoguttata presents multiple marks located in telomeric region on long arm of pairs 1 and 3, in telomeric region on short arm of 7 and 9 pairs and in both regions of the second chromosomic pair. The whole chromosome painting with a probe from the first chromosomic pair showed a share of genomic content between the two Lebiasina species and Boulengerella (Ctenoluciidae), evidencing the close relationship between this two families. Additionally, the comparative genomic hybridization among the two Lebiasina species reveals a high level of genomic differentiation amid them. Another experiment of comparative genomic hybridization reveals a telomeric sex-specific region on the third chromosomic pair of L. bimaculata females. This result with the differential pattern of c-banding, CMA3+ differential stain and the fluorescent in situ hybridization with the microsatellite probe (CGG)n indicates two possibilities (i) the presence of a copy number variation process, generating differences between the homologous pair, or (ii) a nascent sex chromosome system of ZZ/ZW type. Besides that, two chromosomal evolutionary pathways were recognized in Lebiasinidae family, being the first responsible for a probable diploid number conservation in Lebiasininae and, in contrast, an acrocentrization tendency in Pyrrhulininae.